Qualitative insights from an online community-based exercise intervention for persons living with HIV - Ibáñez-Carrasco, Francisco; McDuff, Kiera; Da Silva, George; Bayoumi, Ahmed M.; Chan Carusone, Soo; Loutfy, Mona; Tang, Ada; Ahluwalia, Puja; Avery, Lisa; O’Brien, Kelly K. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionOnline community-based exercise (CBE) is a rehabilitation strategy that can promote health outcomes among people living with HIV. We aimed to describe experiences implementing a community-based exercise (CBE) intervention with adults living with HIV.MethodsWe conducted a longitudinal qualitative descriptive study involving interviews with adults living with HIV and persons implementing an online tele-coaching CBE intervention. Leveraging community-based research principles, the intervention aimed to improve physical activity engagement and health outcomes through online individualized coaching, online YMCA resources, and wearable fitness technology. We analyzed interviews with adults living with HIV and representatives involved in CBE implementation at baseline (month 0), end of intervention (6 months), and end of follow-up phase (12 months).ResultsThirteen adults living with HIV and eight representatives involved in CBE implementation participated in the study (43 interviews total). Key themes included the “four Cs”: Cost, Care, Comfort, and Convenience that encapsulated participants’ perceptions of financial barriers, need for holistic healthcare integration, importance of stigma-free and emotionally supportive environments, and accessibility of health interventions.DiscussionResults underscore the critical role of inclusive and adaptable exercise programs in addressing the complex needs of individuals with chronic, episodic conditions such as HIV, and the value of participatory, community-driven methodologies in designing effective and equitable health interventions.Clinical Trial RegistrationNCT05006391